Environmental estrogens alter early development in Xenopus laevis. - Bevan, Cassandra L (2003)
A growing number of environmental toxicants found in pesticides, herbicides, and industrial solvents are believed to have deleterious effects on development by disrupting hormone-sensitive processes. We exposed Xenopus laevis embryos at early gastrula to the commonly encountered environmental estrogens nonylphenol, octylphenol, and methoxychlor, the antiandrogen, p,p-DDE, or the synthetic androgen, 17 alpha-methyltestosterone at concentrations ranging from 10 nM to 10 microM and examined them at tailbud stages (approximately 48 hr of treatment). Exposure to the three environmental estrogens, as well as to the natural estrogen 17 beta-estradiol, increased mortality, induced morphologic deformations, increased apoptosis, and altered the deposition and differentiation of neural crest-derived melanocytes in tailbud stage embryos. Although neural crest-derived melanocytes were markedly altered in embryos treated with estrogenic toxicants, expression of the early neural crest maker Xslug, a factor that regulates both the induction and subsequent migration of neural crest cells, was not affected, suggesting that the disruption induced by these compounds with respect to melanocyte development may occur at later stages of their differentiation. Co-incubation of embryos with the pure antiestrogen ICI 182,780 blocked the ability of nonylphenol to induce abnormalities in body shape and in melanocyte differentiation but did not block the effects of methoxychlor. Our data indicate not only that acute exposure to these environmental estrogens induces deleterious effects on early vertebrate development but also that different environmental estrogens may alter the fate of a specific cell type via different mechanisms. Finally, our data suggest that the differentiation of neural crest-derived melanocytes may be particularly sensitive to the disruptive actions of these ubiquitous chemical contaminants.